Disability-based labour market inequalities - David Pettinicchio; Michelle Maroto (European Trade Union Institute (ETUI), 2024)
Despite changing attitudes around disability over time, people with disabilities still face large barriers to labour market participation. We apply a sociological framework that considers both supply- and demand-side explanations for labour market inequality to help understand the continuing earnings and employment disparities experienced by people with disabilities across countries. Specifically, we review reemployment disparities across different measures of disability, address sets of individual-level and structural explanations for these disparities, discuss how these explanations interact, and apply them to examples related to intersectionality, unionisation, contingent work, and employment in times of crisis. Paid employment is central to people's social and economic wellbeing within liberal market-based economies, making it important to understand the many dimensions of labour market inequality.
Keywords: 330; Disabled workers; Labor market discrimination; Social inequality; Wage structure; Western Europe; Canada; USA; Behinderte Arbeitskräfte; Arbeitsmarktdiskriminierung; Soziale Ungleichheit; Lohnstruktur; Westeuropa; Kanada; USA